Pengaruh Likuiditas, Profitabilitas, dan Risiko Sistematis terhadap Return Saham pada Perusahaan Energi di Bursa Efek Indonesia periode 2021–2024 - Elis Yusnia; Purwatiningsih Purwatiningsih (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of liquidity (Current Ratio / CR), profitability (Return on Equity / ROE), and systematic risk (Beta) on stock returns in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The research method used is quantitative with an associative approach. Samples were selected using purposive sampling techniques, resulting in 20 companies with a total of 80 observations. Data analysis was carried out through descriptive statistics, classical assumption tests, multiple linear regression, t tests, F tests, and determination coefficient (R²) tests. The results of the study show that partially, liquidity and systematic risk do not have a significant influence on stock returns. On the other hand, profitability (ROE) has been shown to have a significant positive effect on stock returns. Simultaneously, all three independent variables—liquidity, profitability, and systematic risk—affect stock returns, although the dominant contribution comes from profitability. These findings indicate that investors need to pay more attention to profitability indicators in assessing potential stock returns, especially in the energy sector which has characteristics of volatility and dependence on external factors. This research provides practical implications for investors and financial managers in formulating more measurable investment strategies, as well as encouraging the strengthening of fundamental analysis as a basis for investment decision-making in the Indonesian capital market.